3D Printed Mechanically Robust Graphene/CNT Electrodes for Highly Efficient Overall Water Splitting. Issue 23 (4th May 2020) - Peng, Meiwen; Shi, Danli; Sun, Yinghui; Cheng, Jian; Zhao, Bo; Xie, Yiming; Zhang, Junchang; Guo, Wei; Jia, Zheng; Liang, Zhiqiang; Jiang, Lin
Abstract: 3D printing of graphene electrodes with high mechanical strength has been a growing interest in the development of advanced energy, environment, and electronic systems, yet is extremely challenging. Herein, a 3D printed bioinspired electrode of graphene reinforced with 1D carbon nanotubes (CNTs) (3DP GC) with both high flexural strength and hierarchical porous structure is reported via a 3D printing strategy. Mechanics modeling reveals the critical role of the 1D CNTs in the enhanced flexural strength by increasing the friction and adhesion between the 2D graphene nanosheets. The 3DP GC electrodes hold distinct advantages: i) an intrinsically high flexural strength that enables their large‐scale applications; and ii) a hierarchical porous structure that offers large surface area and interconnected channels, endowing fast mass and/or charge and ions transport rate, which is thus beneficial for acting as an ideal catalyst carrier. The 3DP GC electrode integrated with a NiFeP nanosheets array exhibits a voltage of 1.58 V at 30 mA cm −2 as bifunctional electrode for water splitting, which is much better than most of the reported Ni‐, Co‐, and Fe‐based bifunctional electrocatalysts. Importantly, this study paves the way for the practical applications of 3D printed graphene electrodes in many energy conversion/storage, environmental, and electronic systems where high flexural strength is preferred. Abstract : Bioinspired electrodes of 3D printed graphene reinforced by 1D carbon nanotubes (3DP GC), which demonstrate outstanding flexural strength and hierarchical porous structure, are produced via an extrusion‐based 3D printing strategy. The 3DP GC electrodes developed in this work have great potential for a variety of energy conversion and storage, environmental, and electronic applications where high flexural strength and hierarchical porous structure are in pressing demand.